VALIDITAS BAHAN AJAR MICROSOFT POWER POINT – GOOGLE FORM (MC.POINT-GG.FORM) UNTUK PEMBELAJARAN IPA DI SMP NEGERI 1 DRINGU - Retno Irawati (Universitas Jember, 2020)
This research purpose was to produce Microsoft Power Point teaching materials - Google Form (MC.Point-gg.Form) for valid science learning, this teaching material is one of using handphone for the learning process. This teaching material contains static electricity material. This study uses the 4D method (1) define, 2) design, 3) develop and 4) disseminate. This research was applied on one class, IXF which consisted of 32 students. In the teaching material consists of tutorials using MC.Point-gg.Form, learning objectives, material, assessment of pre-test and post-test learning outcomes. The results of the study is in the form of data validation scores for Microsoft Power Point Teaching Materials - Google Form (MC.Point-gg.Form). Evaluation of the validity of teaching materials by experts obtain the following percentage ratings: (1) validation of the material 87,26% with a very valid category, (2) 88,33% programming validation with a very valid category, (3) display validation 90,03% with a very valid category. (4) validation of user responses (teachers) 82% with a very valid category so that Microsoft Power Point and Google Form teaching materials (Mc. Point-gg.form) can be used.